ADCY2 rs10059539 C>T polymorphism confers a decreased risk of hepatocellular carcinoma in Chinese Han women. Issue 5 (September 2021) - Chao, Xu; Miao, Feng; Feng, Xuesong; Shi, Hailong; Wang, Yuewen; Wu, Jieqiong; Zhao, Luyan; Zhang, Wei; Jiang, Chao
Abstract : Objective: Hepatocellular carcinoma (HCC) poses a serious threat to human health. ADCY2 gene polymorphisms may be related to HCC susceptibility. Therefore, we investigated whether ADCY2 gene polymorphisms are correlated to the risk of HCC in a Chinese Han population. Methods: In a case-control study, we examined the associations between single nucleotide polymorphisms (SNPs) in ADCY2 and HCC risk. In 434 HCC cases and 442 healthy controls, we used the Agena MassARRAY platform to select and genotype four tag SNPs in ADCY2 . We used logistic regression after adjusting for age and sex to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results: The results showed that ADCY2 rs10059539 polymorphism was associated with a reduced susceptibility to HCC in women under the dominant model (TC/TT vs. CC; OR = 0.32; 95% CI = 0.13–0.83; P  = 0.018) and the log-additive model (OR = 0.32; 95% CI = 0.13–0.83; P  = 0.018). Conclusions: Our results support the hypothesis that ADCY2 gene polymorphisms influence the genetic susceptibility to HCC. Abstract : Supplemental Digital Content is available in the text.